Resilience On Career Soldier Officer In Indonesian National Armed Forces Headquarters - Sri Mulyani Nasution (Universitas Medan Area, 2021)
Career Soldier Officer Undergraduate Resources experience adversity during the educational process. When they can rise from difficulty, they can be said to have resiliency. This study aims to reveal the resiliency among career soldier Officer Undergraduate Resources within the Indonesian National Armed Forces Headquarters. The design of this research is descriptive quantitative research. Forty officers participated in this research through a purposive sampling technique. Data were collected by using a Likert scale. Product Moment statistical test from Pearson showed a significance level of 5%, r> r table (0.312), valid items 89 out of 144 items. Based on the data analysis, the results (a) Career Soldier Officer Undergraduate Resources overall showed resiliency (b) The officer who has served ten to sixteen years is no more resilient than those who have served less than ten years but is more resilient than those undergoing the service period is more than sixteen years. (c) Internal protective factors were slightly higher than environmental protective factors with a difference in the value of 0.047